Association between periodontal disease and Alzheimer's disease: a scoping review - Zhang, Xiaocui; Huang, Xin; Chang, Mengdie (Frontiers in Aging Neuroscience, 2025)
BackgroundAlzheimer's disease (AD) is the most common type of dementia, with mild cognitive impairment (MCI) as its early reversible stage. Periodontal disease (PD) is a chronic inflammatory condition associated with systemic diseases. Recent studies suggest a potential link between PD and AD/MCI. This scoping review evaluates the existing evidence on the association between PD and AD and explores possible mechanisms.MethodsA literature search was conducted in PubMed, Embase, and Cochrane databases (September 2025), covering studies from 2004 to 2025. Human clinical studies, animal models, and in vitro experiments were included, while reviews were excluded. Two independent researchers performed study selection, data extraction, and quality assessment.ResultsA total of 52 studies were included after screening 1,369 records. Among them, 25 clinical studies examined the PD-AD association, including case-control, cohort, and cross-sectional studies. Additionally, 24 studies investigated underlying mechanisms, and 3 animal studies assessed PD-related interventions for AD. Evidence suggests PD increases the risk of AD and accelerates cognitive decline. Potential mechanisms include amyloid-β (Aβ) and tau protein aggregation, neuroinflammation triggered by Porphyromonas gingivalis (Pg) infection, and gut-brain axis dysregulation. Periodontal treatment and probiotics may have protective effects against AD-related pathology.ConclusionsPD may be a modifiable risk factor for AD, and periodontal interventions could contribute to AD prevention and management. Further clinical studies are needed to confirm the therapeutic potential of targeting oral microbiota in AD.